Analisis Pengaruh Pembelian Online Terhadap Keputusan Pembelian Dengan Minat Beli Sebagai Variabel Intervening - Widodo Wibisono; Moh. Hidayatul Holili (Universitas 17 Agustus 1945 Semarang, 2022)
This study aims to determine the effect of online purchasing on consumer buying interest in buying products online and to determine the effect of online consumer buying interest on consumer purchasing decisions. The data collection technique used a questionnaire instrument with 100 respondents, then collected and checked for validity and then presented in an informative and scientific manner. After that the data is processed in a comprehensive and descriptive-analytic manner. Then the data is tested with SEM (Structural Equation Model) statistics to determine the relationship between various variables. The results of the study state that the first hypothesis which says that online purchases have a positive effect on consumer buying interest online turns out to be significantly proven. This can be seen in table 6.3.1. that the effect of online purchases has a T-statistic value above 1.664 which is equal to 8.086. Meanwhile, the results of the second hypothesis test which says that online consumer buying interest has a positive effect on consumer purchasing decisions has proven to be significant. This can also be seen in table 6.3.1. that consumer buying interest online has a T-statistic value above 1.664, which is 10,799